Quantification of chlorogenic acid and polyphenoloxidase activity in ‘Rocha’ pear after CA long storage - Galvis-Sánchez, A. C. (2011)
The effect of storage time and prevailing storage conditions on the phenolic content and the polyphenol oxidase (PPO) activity of ‘Rocha’ pear were evaluated throughout 9 months of storage. Chlorogenic acid was the dominant phenolic compound quantified in the pulp. Storage time and conditions influenced the acid content and the PPO activity, but a clear tendency could not be observed during storage. By 7 months of storage, the chlorogenic acid content was higher in pears stored under 3%(v/v) O2 + 1.5%(v/v) CO2 than under the other storage conditions. By 9 months of storage, the lowest content of chlorogenic acid was found in pears stored under air. Storage under high CO2 levels was associated with high PPO activities, so it may be a limiting factor in attempts to extend the storage life of ‘Rocha’ pear